The last secret of Fatima my conversations with Sister Lucia - Bertone, Tarcisio 1934-; De Carli, Giuseppe; Benedikt XVI. Papst 1927-2022 (New York [u.a.] Doubleday, 2008)
Under the mantle of Mary -- A perfect post-modern mix -- An illiterate forced to write -- The fateful number thirteen -- Mysterious children -- Encounter with the supernatural -- Not your ordinary red hat -- Parsing the prophecy of Fatima. an interview with Cardinal Tarcisio Bertone -- A radiant, credible witness -- The Rsary and the Liturgy -- The transforming power of Fatima -- John Paul II : the Pope of the third secret -- The enigma of John Paul I -- Envelope, one secret -- Mysteries beyond our ken -- An ongoing revelation -- Fatima, the Holocaust, and more -- Medjugorje -- In defence of popular piety -- Popes and the rosary -- The fascination of the divine -- The call of the sea -- A prayer in the blue mosque -- "As a cardinal, I couldn't say no" -- Messages, interpretations, and acts of entrustment -- The secret of Fatima : parts one and two of the secret -- Supplement to the second part of the secret : the shoah -- Further texts connected with the second secret -- The secret of fatima : the third part of the secret -- Theological commentary of the former prefect of the congregation for the doctrine of the faith, Cardinal Joseph Ratzinger -- John Paul II's act of entrustment to the immaculate heart (March 25, 1984) -- Chronology of the events of Fatima
Includes bibliographical references and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Mary -- Apparitions and miracles -- Portugal -- Fátima; Mary -- Prophecies; Maria Lúcia 1907-2005; Fatima, Our Lady of